The effect of glycerol hyperhydration on Olympic Distance Triathlon performance in high ambient temperatures - Coutts, A.; Reaburn, P.; Mummery, K.; Holmes, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
The purpose of this study was to examine the effect of prior glycerol loading on competitive Olympic distance triathlon performance (ODT) in high ambient temperatures. Ten (3 female and 7 male) well-trained triathletes (VO2max = 58.4 ± 2.4 ml * kg-1 * min-1; best ODT time = 131.5 ± 2.6 min) completed 2 ODTs (1.5-km swim, 40-km bicycle, 10-km run) in a randomly assigned (placebo/glycerol) double-blind study conducted 2 weeks apart. The wet-bulb globe temperature (outdoors) was 30.5 ± 0.5 °C (relative humidity: 46.3 ± 1.1%; hot) and 25.4 ± 0.2 °C (relative humidity: 51.7 ± 2.4%; warm) for day 1 and day 2, respectively. The glycerol solution consisted of 1.2 g of glycerol per kilogram of body mass (BM) and 25 ml of a 0.75 g * kg-1 BM carbohydrate solution (Gatorade®) and was consumed over a 60-min period, 2 hours prior to each ODT. Measures of performance (ODT time), fluid retention, urine output, blood plasma volume changes, and sweat loss were obtained prior to and during the ODT in both the glycerol and placebo conditions. Following glycerol loading, the increase in ODT completion time between the hot and warm conditions was significantly less than the placebo group (placebo 11:40 min vs. glycerol 1:47 min; p < .05). The majority of the performance improvement occurred during the final 10-km run leg of ODT on the hot day. Hyperhydration occurred as a consequence of a reduced diuresis (p < .05) and a subsequent increase in fluid retention (p < .05). No significant differences were observed in sweat loss between the glycerol and placebo conditions. Plasma volume expansion during the loading period was significantly greater (p < .05) on the hot day when glycerol appeared to attenuate the performance decrement in the heat. The present results suggest that glycerol hyperhydration prior to ODT in high ambient temperatures may provide some protection against the negative performance effects of competing in the heat.